Adiponectin/(FBG × FIns) as a predictor of insulin sensitivity and metabolic syndrome in patients with polycystic ovary syndrome. Issue 49 (December 2016) - Xu, Xiaohui; Lai, Yerui; Yang, Gangyi; Yang, Mengliu; Li, Ling; Zhang, Qin; Liu, Hua; Zheng, Hongting; Zhu, Danping
Abstract : Abstract: The euglycemic–hyperinsulinemic clamp is not available in most clinical settings. An accessible and inexpensive measurement for identifying insulin resistance (IR) is necessary. Our aim is to assess whether the adiponectin (ADI) index (ADI/[FBG × FIns]) is a better surrogate index for the assessment of IR or metabolic syndrome (MetS). A population-based cross-sectional study was conducted including 100 healthy women and 99 polycystic ovary syndrome patients. The euglycemic–hyperinsulinemic clamp was performed. Circulating ADI levels were determined by ELISA. Polycystic ovary syndrome and polycystic ovary syndrome plus MetS subjects had higher products of fasting triglycerides and glucose (TyG), Homeostasis Model Assessment of Insulin Resistance (HOMA-IR), increased ratios of the area under the curve for insulin/the area under the curve for glucose (AUCi/AUCg), but lower ADI index as compared with healthy subjects. Partial correlation analysis in all populations showed that the M-value was significantly negatively correlated with HOMA-IR, TyG, TG/HDL, and AUCi/AUCg, and correlated positively with the ADI index. The r value of Pearson correlation between the ADI index and M-value was greater than that of the correlation between HOMA-IR, TyG, TG/HDL-C, and AUCi/AUCg. The optimal cut-off value of the ADI index for detection of IR was 0.67, with a sensitivity of 89.4% and a specificity of 88.1%, whereas for detection of MetS, it was 0.32, with a sensitivity of 88.7% and a specificity of 71.0%. The ADI index may be a surrogate marker in detecting IR and MetS.